Toxicidade e atividade inibitória da carboximetilquitosana isolada e em combinação com sais metálicos na formação de biofilmes por bactérias gram-negativas - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The investigation for alternatives in the control of pathogenic micro-organisms is an interesting field of study. Among the new approaches is the investigation of the antimicrobial action of natural compounds combined with metallic ions. In this context, the objective was to evaluate the inhibitory activity of isolated carboxymethylchitosan or in combination with silver nitrate, copper sulfate and zinc sulfate on biofilm formation by standard strains of Gram-negative bacteria. In this study included the synthesis and characterization of carboxymethylchitosan, determination of the toxicity of the compounds alone and in combination by brine shrimp lethality test, determination of the minimum inhibitory concentration (MIC) and the impact of the isolated compounds and in combination on biofilm formation by detecting the total biomass and cell metabolism associated with the presence of subinibitory concentrations of the compounds. The average degree of substitution of carboxymethylchitosan, as determined by potentiometric titration, was 1.87 and infrared spectroscopy allowed confirmation of the presence of the synthesis reaction. The carboxymethyl-chitosan did not show toxicity to brine shrimp, and salts showed varying degrees of toxicity being observed a reduction of the toxic effects of salts when combined with carboxymethylchitosan. The carboxymethylchitosan had MIC > 1000 μg L-1, the silver nitrate alone and in combination with carboxymethylchitosan CMI = 7.8 μg L-1, in isolated and copper sulphate in combination MIC = 500 mg L-1 and zinc sulfate alone and in combination CMI = 100 μg L-1, except for Pseudomonas aeruginosa which zinc sulfate showed no CMI at the tested concentrations. We identified a significant inhibition of biofilm formation in the presence of carboxymethylchitosan alone and in combination with salts, isolated and detected that the carboxymethylchitosan was the most active in the inhibition by the combination compared with the salts. However, the carboxymethylchitosan combined with the salts showed better inhibitory action when compared to the isolated salts, indicating a possible increase of effect. The results suggest that sub-inhibitory concentrations of these compounds were effective against both the total biomass and the metabolism of the cells associated with biofilm.
Keywords: Carboximetilquitosana; Sais metálicos; Toxicidade; Biofilme; Atividade antimicrobiana; Carboxymethylchitosan; Metal salts; Toxicity; Biofilm; Antimicrobial activity.; CIENCIAS EXATAS E DA TERRA::QUIMICA